Analiza Plastyczna Dwuwarstwowych Powłok Walcowych Uwzględniająca Wpływ Zmian Kształtu - M. Duszek (Engineering Transactions, 1967)
The object of the analysis is the influence on the limit load of a variation of the form of a thin cylindrical sandwich shell. The deflection is assumed to be of the order of the shell thickness. The behaviour of the shells under internal pressure is considered for various mechanical and kinematic boundary conditions. The material the rigid-plastic shell is assumed to have not the strain-hardening property and to obey the Tresca yield condition and the relevant law of flow.